INTERNALISASI NILAI-NILAI MULTIKULTURAL PADA SISWA MELALUI PEMBELAJARAN IPS DI SMP PANGUDI LUHUR DOMENICO SAVIO - Rofik, Muhammad Fathur; Hermanto, Fredy (Universitas Negeri Semarang, 2021)
Pangudi Luhur Domenico Savio Junior High School is a school with a diversity of student backgrounds, from the point of view of religion, ethnicity, socio-economy, and gender / gender. This article aims to Know the process of internalizing multicultural values in students through social studies learning SMP Pangudi Luhur Domenico Savio. The results of this study found that The process of internalizing muticultural values has been carried out by the teacher, the values that are often applied by the teacher are the values of Democratization, Humanism, and Pluralism. which are inserted through various things, namely: (a) Social studies learning materials are formed based on facts and real examples in the field. (b) The learning model used is inquiry discussion with the aim that students better understand the material and can adapt to the surrounding environment. (c) The assessment system used by the teacher is not only in terms of cognitive, affective, and psychomotor, but the assessment also takes into account the opinions of other students regarding the personalities of the students concerned as evaluation materials for the future. SMP Pangudi Luhur Domenico Savio adalah sekolah dengan keberagaman latar belakang peserta didik mulai dari segi agama, etnis, sosial ekonomi, dan jenis kelamin/gender. Artikel ini bertujuan untuk mengetahui proses internalisasi nilai-nilai multikultural pada siswa melalui pembelajaran IPS di SMP Pangudi Luhur Domenico Savio. Hasil dari penelitian ini menemukan bahwa proses internalisasi nilai-nilai mutikultural sudah dilakukan oleh guru, nilai-nilai yang sering diterapkan oleh guru adalah nilai Demokratisasi, Humanis, dan Pluralisme yang disisipkan melalui berbagai hal yaitu: (a) Meteri pembelajaran IPS dibentuk berdasarkan kenyataan dan contoh-contoh nyata yang ada di lapangan. (b) Model pembelajaran yang digunakan diskusi inkuiri dengan tujuan agar peserta didik lebih memahami materi dan dapat beradaptasi dengan lingkungan sekitarnya. (c) Sistem penilaian yang digunakan oleh guru tidak hanya dari segi kognitif, afektif, dan pisikomotorik, akan tetapi penilaian juga mempertimbangakan pendapat dari peserta didik lain terkait kepribadian peserta didik yang bersangkutan sebagai bahan evaluasi untuk kedepannya